Electric-field influence on the neutron diffuse scattering near the ferroelectric transition of Sr0.61Ba0.39Nb2O6. (2nd August 2016) - Ondrejkovic, Petr; Kempa, Martin; Savinov, Maxim; Bednyakov, Petr; Kulda, Jiri; Bourges, Philippe; Dec, Jan; Hlinka, Jirka
ABSTRACT: Uniaxial relaxor ferroelectric Sr0.61 Ba0.39 Nb2 O6 single crystal has been investigated in the vicinity of its phase transition using neutron scattering and dielectric spectroscopy. A global-type thermal hysteresis is evidenced by both techniques in the ferroelectric phase and up to about 15 K above T c . In addition, a part of the transverse neutron diffuse scattering in the 001 Brillouin zone, presumably related to static nanodomain structure, can be suppressed by prior poling the crystal in electric field of 3 kV/cm. The remaining part of the transverse neutron diffuse scattering and the real part of permittivity show a similar temperature dependence. The temperature position of the maximal scattering intensity T max depends significantly on the scattering wave vector. T max shifts monotonically to higher temperature with the increasing wave vector in all investigated cooling and heating regimes. It is concluded that the critical fluctuations have space correlations which depend on frequency and wave vector.